2007
DOI: 10.1073/pnas.0704044104
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signaling is a positive regulator of mammalian cardiac progenitors

Abstract: Guiding multipotent cells into distinct lineages and controlling their expansion remain fundamental challenges in developmental and stem cell biology. Members of the Wnt pathway control many pivotal embryonic events, often promoting self-renewal or expansion of progenitor cells. In contrast, canonical Wnt ligands are thought to negatively regulate cardiomyogenesis in several species. However, the cell-autonomous role of canonical Wnt signaling within precardiac mesoderm, through its obligatory transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
256
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(278 citation statements)
references
References 37 publications
18
256
0
3
Order By: Relevance
“…Similarly, mouse studies have demonstrated that Wnt signals are critical for early cardiac precursor induction and proliferation, but later become inhibitory 28,29 . As previously mentioned, a diverse array of cardiac transcription factors acts in concert with these signals to specify, differentiate, and pattern the developing heart.…”
Section: Complex Signaling and Transcriptional Network Regulate Hearmentioning
confidence: 97%
“…Similarly, mouse studies have demonstrated that Wnt signals are critical for early cardiac precursor induction and proliferation, but later become inhibitory 28,29 . As previously mentioned, a diverse array of cardiac transcription factors acts in concert with these signals to specify, differentiate, and pattern the developing heart.…”
Section: Complex Signaling and Transcriptional Network Regulate Hearmentioning
confidence: 97%
“…The earliest progenitor cell population corresponds to the FHF, which expresses Tbx5 during differentiation and gives rise to the LV (14). The second population identified by Islet-1 expression corresponds to the second heart field (SHF) from which right ventricle, atria, and outflow tract will arise (17,(19)(20)(21). Our findings of the coexpression of ␣MHC and specific cardiac transcription factors like GATA4, and Tbx5 characteristic for the LV, suggest the existence of an ␣MHC pos / cTnT neg cardiac committed FHF stem cell population in the adult heart.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, overexpressing a stabilized version of ␤-catenin under the control of the same enhancer resulted in enlarged ventricular chambers, more cells, and upregulated expression of cyclinD2. 82 Because both chambers were affected, these phenotypes strongly argue that in both cardiac lineages Wnt/␤-catenin signaling supports the expansion of committed cardiac progenitor cells. In contrast, deleting ␤-catenin using a Mesp1 driver mainly affected the SHF but not the FHF.…”
Section: Nkx25-cre-specific Manipulation Of ␤-Catenin Signalingmentioning
confidence: 99%
“…81 The overexpression of ␤-catenin, however, results in an expansion of SHF-derived structures. 79,82 These phenotypes were clearly linked to an effect of Wnt/␤-catenin signaling on cell proliferation. Also in the posterior part of the SHF Wnt signaling regulates cell proliferation.…”
Section: Cardiac Specification: Positive Influence Of Noncanonical Wnmentioning
confidence: 99%